Pembangunan Berbasis Masyarakat Tentang Perubahan Perilaku Menjadikan Tepian Sungai Musi Sebagai Tujuan Wisata Di Kota Palembang - Lisdiana; Nopriawan Mahriadi (Jurnal Pengabdian kepada Masyarakat Radisi, 2021)
Abstract The role of the tourism sector is one of the mainstay sectors for non-oil and gas foreign exchange earnings. Palembang is known as the city of the Batang Hari Sembilan River or what is often called the Musi River, tourism in the Musi River area is one of the main destinations for tourists who come to Palembang, by seeing the potential of the Musi River which is used as a tourist destination. Therefore, the author initiated the creation of a homestay, precisely in the 7 Ulu area of ​​Palembang, this is an effort to build public awareness of the use of riverside tourism as a source of income for the community. The formulation of the problem in this study is how to increase public awareness about the potential of tourism destinations that they have. The purpose of this study is to increase public awareness about the potential of tourism destinations that they have. This study uses a qualitative descriptive method, the subjects in this study are informants who provide data through interviews, the results of this study are the making of homestays as tourist attractions on the Musi River.